Cortisol and 11 beta-hydroxysteroid dehydrogenase type 2 as potential determinants of renal citrate excretion in healthy children - Hua, Yifan; Maser-Gluth, Christiane (Endocrine, 2020)
In patients with Cushing disease, renal citrate excretion is reduced. A low urinary citrate concentration is a risk factor for nephrolithiasis. Since higher acid loading is one major determinant of reduced citrate excretion, we aimed to examine whether glucocorticoids still within the physiological range may already impact on urinary citrate excretion independently of acid-base status. Overall, 132 healthy prepubertal participants of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study who had collected two successive 24-h urine samples (at 1 and 2 years) before the start of their pubertal growth spurt were included in the study. Net acid excretion capacity (NAEC), urinary potential renal acid load (PRAL), creatinine, calcium, and various cortisol metabolites were measured in all samples. Glucocorticoid quantification was done by GC-MS and radioimmunoassay. In regression models multivariable-adjusted for 24-h urinary PRAL, NAEC, creatinine and calcium, urinary free cortisol (UFF), 6β-hydroxycortisol, and 20α-dihydrocortisol showed significant inverse relationships (P ≤ 0.02) with 24-h renal citrate output. By contrast, the estimate of renal 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2), i.e., the ratio of urinary free cortisone/UFF, associated positively with urinary citrate (P = 0.04). In line with studies in hypercortisolic state, even moderately high cortisol levels in healthy children, still within the physiological range, may negatively impact on the kidney’s citrate excretion. Besides, a higher 11β-HSD2 activity, favoring cortisol inactivation, is paralleled by an increased citrate excretion.
Published online: 7 December 2019
Gesehen am 26.03.2020